Prevalência de doenças que simulam câncer de pulmão: experiência de um hospital universitário da região Sul do Brasil - Homrich, Gustavo Köhler (2013)
Introduction: Lung cancer is the most lethal and incidental type of cancer in the world. Several benign lung diseases may mimic lung carcinoma in its clinical and radiological presentation, which makes the differential diagnosis for granulomatous diseases more relevant in endemic regions like Brazil. Justification: There are not many national publications concerning the prevalence of the diseases that mimic lung cancer e and the data from international literature cannot be used in this case because many of these diseases have a variable geographic distribution. Goals: To identify benign diseases that presented themselves as a simulation of a primary lung cancer in patients hospitalized at the University Hospital of Santa Maria (HUSM), to discuss the diagnostic process and to form a profile of regional prevalence. Material and Methods: Transversal study which evaluated the medical records of patients admitted with hypothetical diagnosis of lung cancer between September 2003 and September 2013 at HUSM and, after invasive investigation, were diagnosed with benign disease. Results: The subject population consisted of 804 patients who underwent invasive procedures for suspected lung carcinoma. From all the 804 patients, 622 (77,4%) were confirmed positive for primary lung cancer. A benign disease was confirmed in 54 patients, representing 6,8% of all the analyzed patients and 8% of the diagnoses found. The infectious cause was the most frequent (30 patients), representing 55,6% of the benign diseases - tuberculosis and paracoccidioidomycosis were the most relevant ones, representing 25,9% and 16,7% of the benign diseases respectively. It was not possible to establish a diagnosis for 128 patients (16%). The diagnosis was obtained by flexible bronchoscopy in 30 patients (55,6%) and by thoracotomy in 18 patients (33,4%). Conclusions: There are several benign diseases that present themselves as lung cancer, being the infectious cause the most frequent one. Many of these cases can be diagnosed by minimally invasive procedures such as flexible bronchoscopy. Therefore these diseases should always be included in the diagnostic routine to avoid higher cost procedures and mortality.